Takayasu Arteritis: A Case Presenting With Neurological Symptoms and Proteinuria - Fatma AYDIN; Banu ACAR; Nermin UNCU; Özge BAŞARAN; Elçin ADALET YILDIZ; Alev GÜVEN; Nilgün ÇAKAR (Archives of Rheumatology, 2020)
In this article, we present an 18-year-old female patient who was initially diagnosed as central nervous system vasculitis and focal segmental glomerulosclerosis but later diagnosed as Takayasu arteritis.